Efficacy of a Constructivist Learning Environment on Secondary Students' Connections of the Greenhouse Effect and Global Warming – A Pilot Study - Reinfried, Sibylle; Rottermann, Benno; Aeschbacher, Urs; Huber, Erich (Journal of Geography Education, 2010)
This research project is based on the hypothesis that the understanding of complex concepts in physical geography and the geo sciences warped by popular mental models largely immune to change can be rectified through cognitive conflict strategy. So, for instance, holes in the atmosphere or layers of pollutant gases in the atmosphere are commonly blamed for the greenhouse effect. In order to test whether such lay perceptions can be altered by adequate teaching material, a constructivist learning environment was devised and optimized according to the findings of instructional psychology geared to causing a cognitive conflict and conceptual change. A longitudinal pilot survey using a pretest-posttest design with intervention and a delayed posttest two months later was employed to analyze the efficacy of the constructivist learning environment compared to conventional teaching materials. A total of 41 thirteen-years-old 8th grade students participated. The results of the statistical analysis show that the intervention lead to a significant increase in knowledge and a better understanding of the principle of the greenhouse effect in the experimental group in the posttest as well as in the delayed posttest. These results are of considerable significance because none of the attempted treatments published so far have succeeded in bringing about long-term conceptual change.